The code of the Samurai - Daidoji, Yuzan (Charles E. Tuttle Company, 1988)
This book, written over 400 years ago, is a unique treatise on the rules by which Japan's aristocratic warrior class lived and worked. Traces of this ancient culture are found in Japan even today